2008
DOI: 10.1116/1.2819268
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of vanadium dioxide thin films prepared by reactive-biased target ion beam deposition

Abstract: Using a novel growth technique called reactive bias target ion beam deposition, the authors have prepared highly oriented VO2 thin films on Al2O3 (0001) substrates at various growth temperatures ranging from 250to550°C. The influence of the growth parameters on the microstructure and transport properties of VO2 thin films was systematically investigated. A change in electrical conductivity of 103 was measured at 341K associated with the well known metal-insulator transition (MIT). It was observed that the MIT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 25 publications
0
57
0
Order By: Relevance
“…The film was synthesized using the Reactive Biased Target Ion Beam Deposition (RBTIBD) method. 22 The growth conditions for optimal stoichiometry are the same as those reported elsewhere. 23,24 An atomic force microscope image of the sample, shown in Fig.…”
Section: A Sample Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The film was synthesized using the Reactive Biased Target Ion Beam Deposition (RBTIBD) method. 22 The growth conditions for optimal stoichiometry are the same as those reported elsewhere. 23,24 An atomic force microscope image of the sample, shown in Fig.…”
Section: A Sample Characterizationmentioning
confidence: 99%
“…22 The growth conditions for optimal stoichiometry are the same as those reported elsewhere. 23,24 An atomic force microscope image of the sample, shown in Fig. 1(b), indicates that the VO 2 film consists of many individual grains with an in-plane size of about 100 nm.…”
Section: A Sample Characterizationmentioning
confidence: 99%
“…The systematic study of growth conditions can be found elsewhere. [16] The Raman spectroscopy with a 488 nm laser source, was conducted at room temperature and at 150 °C. To characterize the transport behavior of the films, photolithography was used to fabricate 250 × 250 µm 2 top contacts with a separation of 5 µm.…”
Section: Methodsmentioning
confidence: 99%
“…Under almost six decades of intense studies, VO 2 has been fashioned into a diverse range of forms such as bulk crystals [4,18,19], amorphous or highly oriented films [20][21][22], and nano-/micro-crystals [23][24][25][26][27]. Although the growth of low strain, free-standing single crystals is readily accomplished via solution growth [28,29], the growth of high quality crystalline films has not been possible until recently with developments in epitaxial techniques [21,30]. Amongst these samples, the macroscopically measured metalinsulator transition (MIT) temperature, T MIT , can vary by up to 100 K [20,22,29,31,32].…”
Section: Introductionmentioning
confidence: 99%